Affliction health, disease, poverty - Das, Veena 1945- (Fordham University Press, 2015)
"Affliction: Health, Disease, Poverty inaugurates a novel way of understanding the trajectories of health and disease in the context of poverty. It traces the unfolding of illness within families, local communities, neighborhood markets and in occult worlds. Privileging the experience of people living in these neighborhoods it asks how can global health be made to take this experience into account rather than escape from it?"--Provided by publisher
Description based on print version record
Keywords: Poverty